Aluminium oxidation at high anodic potentials in an AlCl 3-containing air- and water-stable ionic liquid solution - Veder, Jean-pierre; Horne, M.; Rüther, T.; Bond, A.; Rodopoulos, T. (Elsevier Inc., 2013)
The observation of a multi-step stripping process at high positive potentials is reported for aluminium electrodeposition from a solution of AlCl3 in the air- and water-stable ionic liquid 1-butyl-1- methylpyrrolidinium bis(trifluoromethylsulfonyl)imide. Cyclic voltammograms recorded on an aluminium-coated boron-doped diamond electrode revealed complex oxidative behaviour, suggesting that a passive layer forms on the freshly deposited aluminium that hinders electro-oxidation. High positive potentials are required to induce chloride attack of the passive film, composed of Al-NTf 2 compounds, and facilitate the rapid oxidation of the underlying aluminium metal. These results have important implications in bipolar-pulse electroplating and electrorefining applications where electrodissolution of aluminium is required. © 2013 Published by Elsevier B.V. All rights reserved.